The fragile threads of power ebook - Schwab, V. E. (Threads of Power, 2023)
A New York Times Bestseller A USA Today Bestseller September IndieNext Pick A new door opens... Once there were four worlds, nestled like pages in a book, each pulsing with fantastical power and connected by a single city: London. After a desperate attempt to prevent corruption and ruin in the four Londons, there are only three: ● Grey London, thriving but barely able to remember its magical heritage ● Red London, ruled lately by the Maresh family, flourishing and powerful ● White London, left to brutality and decay Now the worlds are going to collide anew—brought to a dangerous precipice by the discoveries of three remarkable magicians. There's Kosika, the child queen of White London, who has nourished her city on blood and dreams—and whose growing devotion to both is leading her down a dangerous path. Then there's Delilah Bard, born a thief in Grey London, who crossed the worlds to become a legend far from there. She's an infamous magician, a devious heroine, and a risk-taking rogue, all rolled into one unforgettable package. Having disappeared to seek new adventure, an old favor now calls Lila back to a dangerous port, to join some old friends who need more help than they realize. Last there is Tes, a young runaway with an unusual and powerful ability, hiding out in Red London while trying to stay out of the limelight. Tes is the only one who can keep all the worlds from unraveling—if she manages to stay alive first. From #1 New York Times bestselling author V. E. Schwab comes a new adventure set in a beloved world—where old friends and foes alike are faced with a dangerous new threat. PopSugar , This Year's Best New Fantasy Paste Magazine , Most Anticipated Fantasy Books of Fall The Washington Post , 10 Noteworthy Books for September Goodreads, Readers' Most Anticipated Books of Fall Polygon , Best New SFF for the Fall EW.com, Fall Book Must-Reads At the Publisher's request, this title is being sold without Digital Rights Management Software (DRM) applied.